Complex Coacervation: Underwater Adhesion of Multiresponsive Complex Coacervates (Adv. Mater. Interfaces 4/2020). Issue 4 (21st February 2020) - Dompé, Marco; Cedano‐Serrano, Francisco J.; Vahdati, Mehdi; van Westerveld, Larissa; Hourdet, Dominique; Creton, Costantino; van der Gucht, Jasper; Kodger, Thomas; Kamperman, Marleen
Abstract : The image represents a complex coacervate‐based adhesive which can be injected through a syringe (1) on a tissue wound. When released in a physiological environment, the liquid adhesive turns into a solid (2). The liquid‐to‐solid transition is exclusively ascribed to the formation of non‐covalent interactions, e.g. electrostatic and hydrophobic (3), between the polymer chains constituting the material. More details can be found in article number 1901785 by Marco Dompé, Marleen Kamperman, and co‐workers.